A Preliminary Quantitative Electron Microscopic Analysis Reveals Reduced Number of Mitochondria in the Infralimbic Cortex of Rats Exposed to Chronic Mild Stress - Csabai, Dávid; Sebők-Tornai, Abigél; Wiborg, Ove; Czéh, Boldizsár (Frontiers in Behavioral Neuroscience, 2022)
Exposure to severe, uncontrollable and long-lasting stress is a strong risk factor for the development of numerous mental and somatic disorders. Animal studies document that chronic stress can alter neuronal morphology and functioning in limbic brain structures such as the prefrontal cortex. Mitochondria are intracellular powerhouses generating chemical energy for biochemical reactions of the cell. Recent findings document that chronic stress can lead to changes in mitochondrial function and metabolism. Here, we studied putative mitochondrial damage in response to chronic stress in neurons of the medial prefrontal cortex. We performed a systematic quantitative ultrastructural analysis to examine the consequences of 9-weeks of chronic mild stress on mitochondria number and morphology in the infralimbic cortex of adult male rats. In this preliminary study, we analyzed 4 250 electron microscopic images and 67 000 mitochondria were counted and examined in the brains of 4 control and 4 stressed rats. We found significantly reduced number of mitochondria in the infralimbic cortex of the stressed animals, but we could not detect any significant alteration in mitochondrial morphology. These data support the concept that prolonged stress can lead to mitochondrial loss. This in turn may result in impaired energy production. Reduced cellular energy may sensitize the neurons to additional injuries and may eventually trigger the development of psychopathologies.